FINTECH COMPANIES AND THEIR INTERACTION WITH BANKS: INTERNATIONAL AND RUSSIAN EXPERIENCE - S. S. Matveevskii; A. V. Berdyshev (Вестник университета, 2020)
The paper examines the features of interaction between FinTech companies and banks abroad and in Russia. The authors conclude that the development and transformation of a FinTech company into neo-banks is associated with an increase in financial services for companies, successful capital raising, cooperation with banks and the use of specialized platforms. It is emphasized that abroad there is active competition and cooperation between BigTech and FinTech companies, neo-banks and traditional banks; in Russia, in the context of the active digital transformation of Sberbank and other large banks, FinTech companies are active only in the P2P and P2G payment segments. The authors emphasize the importance of banking ecosystems that transform modern Russian banks into universal platforms that provide partners and clients with a variety of services. As a result, further intensification of competition between BigTech and FinTech companies, neo-banks, as well as banks that have undergone digital transformation, in the monetary sphere, both in national and international markets, should be expected.